Can we get back together? Measuring brand relationship breakup. Issue 3 (9th November 2020) - Lopez, Alberto
Abstract: The phenomenon of consumers developing relationships with brands is well documented. However, few researchers have addressed the brand relationship breakup process. Since consumers choose to break up with brands for several reasons, the purpose of this study is to better understand brand relationship breakups and reconciliation through the development and validation of a measure of the valence of the brand relationship breakup (i.e., how positively, negatively, or neutrally the consumer perceives the brand relationship breakup). The findings indicate that a more positive brand relationship breakup makes consumers more prone to reconcile with the brand and less likely to spread negative word of mouth. In addition, consumer desire for vengeance mediates this relationship. Finally, this paper explores how the valence of a brand relationship breakup influences the type of recovery strategies a company should use to reestablish the brand relationship with the consumer.